Enfoque criminológico en la investigación científica de la nueva realidad criminal - Vega Figueroa, Enver (Archivos de criminología, seguridad privada y criminalística, 2020)
Given the complexity of the antisocial behavioral phenomena manifested in Peru's new criminal reality, it is essential to generate empirical evidence and scientific knowledge that supports the design of policies and strategies, as well as the taking of government decisions on public safety.